Inhibition of peptidyl-prolyl isomerase (PIN1) and BRAF signaling to target melanoma - Braun, Christina; Schneider, Nadja; Pei, Dehua; Boßerhoff, Anja Katrin; Kuphal, Silke (American Journal of Translational Research, 2019)
PIN1 is a phosphorylation-dependent peptidyl-prolyl cis/trans isomerase, overexpressed in many cancers, including melanoma. Our immunohistochemistry data of melanoma patient tissue underline the up-regulation of PIN1 in metastases. Here, we demonstrate important functions of PIN1 and its selective and cell permeable inhibitor 37 for the treatment of melanoma. To analyze its possible role in oncogenesis and as a therapeutic target, we first suppressed PIN1 expression by a siRNA pool. PIN1 knockdown potently inhibited melanoma cell proliferation and vascular mimicry by influencing several cancer-relevant pathways. Furthermore, inhibitor 37 inhibited cell growth in melanoma and induced apoptosis. Normal healthy melanocytes, keratinocytes and fibroblasts are not affected by the PIN1 inhibitor 37. Combinatorial treatment of melanoma cells is with Vemurafenib as a common therapeutic option for BRAF-mutated melanoma and inhibitor 37 resulted in a strong, synergistic effect on apoptosis of melanoma cell lines. In summary, targeting PIN1 offers a promising therapeutic approach to simultaneously downregulate multiple cancer-driving pathways in cancer.
CRIS-Team WoS Importer:2019-08-09